Wintertime characteristics of aerosols at middle Indo-Gangetic Plain: Impacts of regional meteorology and long range transport. (March 2015) - Kumar, M.; Tiwari, S.; Murari, V.; Singh, A.K.; Banerjee, T.
Abstract: To develop a coherent picture of possible origin of Asian aerosol, transport and meteorological interaction; wintertime aerosol (January, 1 to March, 31, 2014 (n = 90)) were measured in middle IGP in terms of aerosol mass loading, optical properties, altitudinal distributions and both high and low altitude transportation. Both space-borne passive (Aqua and Terra MODIS) and active sensor (CALIPSO-CALIOP) based measurements were concurrently used over the selected transect (25°10′–25°19′N and 82°54′–83°4′E). Exceptionally high aerosol mass loading was recorded for PM10 (233 ± 58.37 μg m −3 ) and PM2.5 (138 ± 47.12 μg m −3 ). Daily variations of PM2.5 /PM10 persist in a range of 0.25–0.97 (mean = 0.60 ± 0.14; n = 90) and were in accordance to computed Angstrom exponent (0.078–1.407; mean: 1.002 ± 0.254) explaining concurrent contribution of both PM2.5 and PM10 for the region. Space borne (Aqua MODIS-AOD: 0.259–2.194) and ground based (MTP-AOD: 0.066–1.239) AODs revealed significant temporal variability and moderate association in terms of PM10 (MODIS-AOD: 0.46; MTP-AOD: 0.56) and PM2.5 (MODIS-AOD: 0.54; MTP-AOD: 0.39). Varying association of AOD and aerosol mass loading was also explained in terms of meteorological variables. CALIPSO altitude-orbit-cross-section profiles revealed presence of non-spherical coarse particulates (altitude: 1.2–5.4 km) and dominance of spherical fine particulates (altitude: 0.1–4.2 km). Contribution of trans-boundary aerosols transportation to mass loadings at middle IGP were recognized through lagrangian particle dispersion model, synoptic vector wind profiles at different geopotential heights and satellite images. Highlights: Exceptionally high aerosol mass loading for both PM10 and PM2.5 at middle IGP. Space borne & ground based AOD reveal variability and moderate association with PM. CALIPSO cross-section profiles depicts altitudinal distributions of aerosols. At lower altitude continental wind accumulate fine PM from north-western dry part. At higher altitude coarser PM accumulate due to strong intercontinental westerly. Abstract : Exceptionally high aerosol loading found moderately correlated with meteorology, space-borne and ground-based AODs; deposited in varying altitudes and governed by synoptic wind pattern.